Imaging Inflammation in a Patient with Epilepsy Due to Focal Cortical Dysplasia. Issue 1 (11th January 2011) - Butler, Tracy; Ichise, Masanori; Teich, Andrew F.; Gerard, Elizabeth; Osborne, Joseph; French, Jacqueline; Devinsky, Orrin; Kuzniecky, Ruben; Gilliam, Frank; Pervez, Fahad; Provenzano, Frank; Goldsmith, Stanley; et al.
Abstract : ABSTRACT: BACKGROUND AND PURPOSE: Evidence from animal models and examination of human epilepsy surgery specimens indicates that inflammation plays an important role in epilepsy. Positron emission tomography (PET) using [C11]PK11195, a marker of activated microglia, provides a means to visualize neuroinflammation in vivo in humans. We hypothesize that in patients with active epilepsy, [C11]PK11195 PET (PK‐PET) may be able to identify areas of focally increased inflammation corresponding to the seizure onset zone. METHODS: A young woman with intractable epilepsy underwent PK‐PET as part of an approved research study. PK‐PET results were compared with results from other clinical studies. RESULTS: PK‐PET revealed an area of focally increased radiotracer uptake in the right frontal lobe corresponding to this patient's seizure focus as identified by ictal and interictal 18F‐fluorodeoxyglucose (FDG)‐PET and EEG. Routine brain magnetic resonance imaging (MRI) was initially considered normal, though high‐resolution studies showed possible subtle dysplasia of the right frontal lobe. The patient underwent a right frontal lobe resection, and pathological evaluation showed focal cortical dysplasia with activated microglia. CONCLUSIONS: PK‐PET can identify neuroinflammation associated with subtle focal cortical dysplasia, and may therefore have a clinical role in guiding epilepsy surgery for patients with difficult‐to‐localize seizure foci.